A secure biometrics-based authentication key exchange protocol for multi-server TMIS using ECC. (October 2018) - Qi, Mingping; Chen, Jianhua; Chen, Yitao
Highlights: A secure biometrics-based authentication key exchange protocol for multi-server TMIS using elliptic curve cryptography is proposed. Unlike some relevant existing schemes, the registration center of the proposed scheme needn't to share system private key with distributed servers. The security analysis by BAN logic and heuristic cryptanalysis shows the proposed scheme is a secure authentication scheme for multi-server TMIS. Abstract: Background and objectives: Telecare Medicine Information System (TMIS) enables physicians to efficiently and conveniently make certain diagnoses and medical treatment for patients over the insecure public Internet. To ensure patients securely access to medicinal services, many authentication schemes have been proposed. Although numerous cryptographic authentication schemes for TMIS have been proposed with the aim to ensure data security, user privacy and authentication, various forms of attacks make these schemes impractical. Methods: To design a truly secure and practical authentication scheme for TMIS, a new biometrics-based authentication key exchange protocol for multi-server TMIS without sharing the system private key with distributed servers is presented in this work. Results: Our proposed protocol has perfect security features including mutual authentication, user anonymity, perfect forward secrecy and resisting various well-known attacks, and these security feathers are confirmed by the BAN logic and heuristic cryptanalysis, respectively. Conclusions: A secure biometrics-based authentication key exchange protocol for multi-server TMIS is presented in this work, which has perfect security properties including perfect forward secrecy, supporting user anonymity, etc., and can withstand various attacks such as impersonation attack, off-line password guessing attack, etc.. Considering security is the most important factor for an authentication scheme, so our scheme is more suitable for multi-server TMIS.